Highly active probiotic hydrogels matrixed on bacterial EPS accelerate wound healing via maintaining stable skin microbiota and reducing inflammation - Hongtao Xu; Yaqian Li; Jiangping Song; Liuyang Zhou; Kaizhang Wu; Xingyu Lu; XiaoNing Zhai; Zhili Wan; Jie Gao (Bioactive Materials, 2024)
Skin microbiota plays an important role in wound healing, but skin injuries are highly susceptible to wound infections, leading to disruption of the skin microbiota. However, conventional antibacterial hydrogels eliminate both probiotics and pathogenic bacteria, disrupting the balance of the skin microbiota. Therefore, it is important to develop a wound dressing that can fend off foreign pathogenic bacteria while preserving skin microbiota stability. Inspired by live bacteria therapy, we designed a probiotic hydrogel (HAEPS@L.sei gel) with high viability for promoting wound healing. Lactobacillus paracasei TYM202 encapsulated in the hydrogel has the activity of promoting wound healing, and the hydrogel matrix EPS-M76 has the prebiotic activity that promotes the proliferation and metabolism of Lactobacillus paracasei TYM202. During the wound healing process, HAEPS@L.sei gel releases lactic acid and acetic acid to resist the growth of pathogenic bacteria while maintaining Firmicutes and Proteobacteria balance at the phylum level, thus preserving skin microbiota stability. Our results showed that live probiotic hydrogels reduce the incidence of inflammation during wound healing while promoting angiogenesis and increasing collagen deposition. This study provides new ideas for developing wound dressings predicated on live bacterial hydrogels.